A starting guide to root ecology: strengthening ecological concepts and standardising root classification, sampling, processing and trait measurements. Issue 3 (5th October 2021) - Freschet, Grégoire T.; Pagès, Loïc; Iversen, Colleen M.; Comas, Louise H.; Rewald, Boris; Roumet, Catherine; Klimešová, Jitka; Zadworny, Marcin; Poorter, Hendrik; Postma, Johannes A.; Adams, Thomas S.; Bagniewska‐Zadworna, Agnieszka; et al.
Summary: In the context of a recent massive increase in research on plant root functions and their impact on the environment, root ecologists currently face many important challenges to keep on generating cutting‐edge, meaningful and integrated knowledge. Consideration of the below‐ground components in plant and ecosystem studies has been consistently called for in recent decades, but methodology is disparate and sometimes inappropriate. This handbook, based on the collective effort of a large team of experts, will improve trait comparisons across studies and integration of information across databases by providing standardised methods and controlled vocabularies. It is meant to be used not only as starting point by students and scientists who desire working on below‐ground ecosystems, but also by experts for consolidating and broadening their views on multiple aspects of root ecology. Beyond the classical compilation of measurement protocols, we have synthesised recommendations from the literature to provide key background knowledge useful for: (1) defining below‐ground plant entities and giving keys for their meaningful dissection, classification and naming beyond the classical fine‐root vs coarse‐root approach; (2) considering the specificity of root research to produce sound laboratory and field data; (3) describing typical, but overlooked steps for studying roots (e.g. root handling, cleaning and storage); and (4) gathering metadata necessary for the interpretation of results and their reuse. Most importantly, all root traits have been introduced with some degree of ecological context that will be a foundation for understanding their ecological meaning, their typical use and uncertainties, and some methodological and conceptual perspectives for future research. Considering all of this, we urge readers not to solely extract protocol recommendations for trait measurements from this work, but to take a moment to read and reflect on the extensive information contained in this broader guide to root ecology, including sections I–VII and the many introductions to each section and root trait description. Finally, it is critical to understand that a major aim of this guide is to help break down barriers between the many subdisciplines of root ecology and ecophysiology, broaden researchers' views on the multiple aspects of root study and create favourable conditions for the inception of comprehensive experiments on the role of roots in plant and ecosystem functioning.